БЎЛАЖАК ЎҚИТУВЧИНИНГ АКМЕОЛОГИК МЕХАНИЗМЛАРИНИ РИВОЖЛАНТИРИШ - Даукеева, А. (SCIENCE and SOCIETY, 2022)
Acmeological competence of the future teacher's development is defined as the unity of theoretical and practical training and the ability to professionally carry out professional activities.
Keywords: future teacher's; acmeological; competence; theoretical and practical training